Depression is associated with poor control of symptoms in asthma and rhinitis: A population-based study. (August 2019) - Grosso, Amelia; Pesce, Giancarlo; Marcon, Alessandro; Piloni, Davide; Albicini, Federica; Gini, Erica; Marchetti, Pierpaolo; Battaglia, Salvatore; Ferrari, Marcello; Fois, Alessandro; Piccioni, Pavilio; Antonicelli, Leonardo; et al.
Abstract: Background: Although many studies have highlighted the link between asthma/rhinitis and depression, it is still unclear which characteristics of these diseases are associated with the risk of depression. We aimed to explore the relationship between depression and asthma or rhinitis in a representative sample of the Italian general population. Methods: The data were collected in GEIRD, an Italian multicenter, population-based, multicase-control study. 2227 participants (age 21–86 years, female 50%) underwent standardized interviews, skin prick and lung function tests, and were divided into cases of current asthma (n = 528), rhinitis without asthma (n = 972), and controls (n = 727). Two specific questions from the Patient Health Questionnaire (PHQ-2) were asked to identify symptoms of depressed mood and anhedonia, which were used as a proxy of major depression disorder. Results: The prevalence of depression was 16.7%, 11.9%, and 5.1% in subjects with asthma, rhinitis and controls, respectively. Both in asthma and rhinitis, subjects with depression had worse respiratory-health related quality of life and more frequent disease-related symptoms than their non-depressed counterparts. In asthma, depression was associated with poorer disease control. In rhinitis, depression was significantly associated with a disease-related limitations in daily activities and greater risk of symptom exacerbations and prescriptions of medicines for breathing. Cases of rhinitis with depression were less likely to be atopic. Conclusions: Our results suggest that rhinitis exacerbations, particularly in non-atopic subjects, and low asthma control are strongly related to the presence of depressed mood in adults from the general population. Highlights: The 17% of asthmatics suffer of depression in the Italian general population. A relation between worse asthma control and depression status has been found. The prevalence of depression is 12% among adults with rhinitis. Rhinitis exacerbations, mostly in non-atopic subjects, is related to depression. A multidimensional approach to health care should be considered in these patients.